Against all enemies - Clancy, Tom, 1947-2013 (G.P. Putnam's Sons, 2011)
For years, ex-Navy SEAL Maxwell Moore has worked across the Middle East and behind the scenes for the Special Activities Division of the CIA, making connections, extracting valuable intelligence, and facing off against America's enemies at every turn. When Moore arrives at a rendezvous to take charge of a high-ranking Taliban captive, the meeting takes a horrific turn.